Exploring Acrylamide and 5-Hydroxymethylfurfural Formation in Glucose-Asparagine-Linoleic Acid System With a Kinetic Model Approach - Ma, Yingjie; Long, You; Li, Feng; Zhang, Yan; Gan, Bei; Yu, Qiang; Xie, Jianhua; Chen, Yi (Frontiers in Nutrition, 2022)
In the "glucose-asparagine-linoleic acid" ternary system, a kinetic model approach was used to explore formation and elimination law of target hazards, including acrylamide (AA) and 5-hydroxymethylfurfural (5-HMF), and their related precursors and intermediate products. The results showed that the elimination of glucose and asparagine and the formation of fructose (generated from glucose isomerization), 3-deoxyglucosone (3-DG), methylglyoxal (MGO), and glyoxal (GO), AA and 5-HMF followed first-order reaction kinetics with high fit coefficients (R2 > 0.9). In addition, the kinetic reaction rate constants increased as the increasing temperature, and all models followed the Arrhenius law. Results of statistical correlations analysis suggested that at lower temperature, the generic amino acid route and the specific amino acid route may paly crucial roles for the formation of AA and 5-HMF, while at high temperature a linoleic acid pathway may be predominantly involved.